A Simple Method for Preparing Fibrinogen - Straughn, W, III; Wagner, R. H (Thrombosis and Haemostasis, 1966)
A simple new procedure is reported for the isolation of canine, bovine, porcine, and human fibrinogen. Two molar β-alanine is used to precipitate fibrinogen from barium sulfate adsorbed plasma. The procedure is characterized by dependability and high yields. The material is 95% to 98% clottable protein but still contains impurities such as plasminogen and fibrin-stabilizing factor. Plasminogen may be removed by adsorption with charcoal. The fibrinogen preparations exhibit marked stability to freezing, lyophilization, and dialysis. Epsilon-amino-n-caproic acid and gamma-aminobutyric acid which were also studied have the property of precipitating proteins from plasma but lack the specificity for fibrinogen found with β-alanine.